Abnormal Readings in the Holy Quran and their Impact on Grammatical Studies - Jaad, Asmaa Muhammad Sulaiman (Dzil Majaz: Journal of Arabic Literature, 2023)
The Quranic recitations, its frequent and irregular ones, are considered an important source in revealing the meanings of the verses of the wise remembrance. That is why the commentators paid great attention to studying these readings because they have a great impact in highlighting an aspect of the miraculousness of the book of God - Glory be to Him - which appears in its connection with the Arabic language in general and grammar in particular, so the research came to shed light on part of this subject and reveal one of its secrets except It is the study of abnormal readings and their impact on grammatical studies. Applying this to (semi-sentence and related provisions). The research adopted the descriptive approach in terms of explaining the concept of abnormal Quranic readings and their impact on the grammatical lesson, applying some semi-sentence images in the verses of the Holy Quran. This is by referring to the sources that are specialized in Quranic readings and their divisions, and relying on the sources that include talking about abnormal readings from them and studying them in a grammatical study by deducing the aspects of the influence of grammatical rules on them, and applying that to the semi-sentence and related provisions as a model.